The Implementation of Project Based Learning with Lesson Study Approach on Human Respiratory System Material to Improve Critical Thinking Skills - Ruswita Prawida Lestari; Natalia Rosa Keliat; Marisa Christina Tapilouw (Bioeducation Journal, 2023)
The common problem encountered in learning is the use of inappropriate learning models. Based on the results of interviews with teachers, known that teachers use less varied models and often use the lecturing method. This condition causes the critical thinking skills of the students not well developed. The purpose of the study is to determine the impact and difference of the PjBL model implementation with the Lesson Study approach on students' critical thinking skills in the human respiratory system lesson. The research method used in this research is descriptive quantitative. The research design used a pretest-posttest control group design involving two classes: the experimental class and the control class. Analysis of students' critical thinking skills using inferential statistics was carried out with the Paired t-test, Independent t-test, and the N-Gain Score. The results of this study showed that the data was distributed normally but not homogeneous, then it was followed by a nonparametric test. Based on the results of the Wilcoxon test, a p-value of 0.001 is obtained, which means that there is an influence of the PjBL model with LS on critical thinking skills. The results of the Mann-Whitney test obtained a p-value of 0.00, which means that there is a significant difference in the average value of the critical thinking skills. The results of the N-Gain score in the experimental class obtained the value of 0.76 (high). Meanwhile, in the control class, the value of 0.34 (medium) is obtained.